Spatial-temporal evolution of tuberculosis incidence rates in indigenous and non-indigenous people of Brazil, from 2011 to 2022 - Isabela Freitas Vaz; Natália Santana Paiva; Paulo Victor de Sousa Viana (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To describe the space-time evolution of TB incidence rates (TI) in indigenous and non-indigenous people, according to the Federative Units (UF) of Brazil, from 2011 to 2022. Methods: Ecological, temporal, and spatial study on new tuberculosis cases in Brazil among indigenous and non-indigenous populations. Data from the Notifiable Diseases Information System (Sinan) were collected from 2011 to 2022 and stratified by Federal Unit, explored and statistically analyzed using R software version 4.2.3. Results: The mean TI among indigenous populations in Brazil was 71.7 new cases per 100,000 inhabitants, while for non-indigenous populations it was 28.6/100,000 inhabitants. The regions of the country that presented the highest (mean) incidence among indigenous populations were: Central-West (102.8/100,000 inhabitants), Southeast (99.6/100,000 inhabitants), and North (79.9/100,000 inhabitants). For non-indigenous populations the highest incidence was in the North region (36.5/100,000 inhabitants), followed by the Southeast (31.3/100,000), and the Northeast (27,4/100,000 inhabitants). The analysis showed that the highest incidence of TB cases among indigenous populations occurred in the states of: SP, RO, RJ, MS, MT e PA. Conclusion: High incidence of the disease compared to the non-indigenous population show the need for a specific approach to address the health needs of these populations. Regional disparities in incidence indicate the need to address socioeconomic and infrastructure issues that affect the health of indigenous populations.